55.7k views
5 votes
Explain the steps that are necessary to solve 4x - 2(x + 3) = x + 1

User Psmith
by
5.7k points

2 Answers

6 votes
First distribute
4x-2x-6=x+1
Then combine like terms
2x-6=x+1
Subtract one from both sides
2x-7=x
Subtract the 2x
-7=-x
Divide both side by negative 1
7=x
User Yansigner
by
6.2k points
2 votes
so you would distribute what's in the parenthesis and end up with 4x-2x-6=x+1, then you combine like terms and end up with 2x-6=x+1, now you can add 6 to both sides or subtract 1 both sides (basically anything goes for this step just make sure you apply the same thing on both sides) so I'll add 6 and continue just to show you... then you end up with 2x=x+7 then you subtract 1x on both sides to get x=7. sorry it's a lot hopefully you get it know!
User Pymarco
by
5.5k points